Degeneration Cortico - Striatal Type of Creutzfeldt- Jakob - Silberman S., Jacobo (1963)
This article presents the clinical and pathological findings presenile 3 patients who died between 4 and 9 1/2 months of the start of a osteotendinous subacute disease characterized clinically by desarroll0 progressively faster, mental deterioration, generalized rigidity , hyperreflexia and tremor of the fingers . One patient , who also showed signs of bilateral Babinski , also showed sintomotoloqía of cerebellar dysfunction and in another of them the clinical examination revealed a type cerebral blindness . In all three cases the cerebro spinal fluid was normal characteristics ; electroencephalogram suggested diffuse cerebral dysfunction and pneumoencéfalograma showed moderate but generalized ventricular enlargement . At pathologic examination , the three brains were externally negatives and coronal sections of them , only showed a moderate dilatation of the lateral ventricles . Microscopically, we observed a marked hypertrophy and hyperplasia astrocyte present in regions of the neo - cortex , neo- striatum , anterior nucleus of the optic thalamus , hypothalamus and colliculi but absent or minimal in regions archicortex , globus pallidum and other portions of optic thalamus and brainstem. All of these areas , either those with astrocytic changes as you do not show , however , showed a nonspecific neuronal degeneration, moderate and approximately equal intensity in all of them and likewise revealed discrete changes in axons , myelin sheaths or other neural structures. In one case the degree of neuronal commitment was particularly intense in the occipital cortex possibly conditioning the cortical blindness that this patient and in another , a loss moderate to strong granular cells and Purkinje cerebellar cortex was related possibly cerebellar symptoms to said patient presented . This pattern of changes hístolócicos may well outline a specific entity within the heterogeneous group of cases currently included in Creutzfeldt-Jakob syndrome and on the other hand suggest the possibility that the observed changes in astrocytes, represent a primary reaction or better still a reaction to a direct deleterious effect of pathogenetic factors operative in these cases ; only a secondary phenomenon either neuronal changes or other components of the central nervous system.